2015
DOI: 10.1142/s021881041550015x
|View full text |Cite
|
Sign up to set email alerts
|

Factors Affecting the Functional Results of Open Reduction and Internal Fixation for Fracture-Dislocations of the Proximal Interphalangeal Joint

Abstract: To clarify the factors affecting functional results of fracture-dislocations of the proximal interphalangeal (PIP) joint treated by open reduction and internal fixation (ORIF), 60 patients, including 38 patients with a dorsal fracture-dislocation and 22 with a pilon fracture, were analysed. The mean ratio of articular surface involvement was 48.5% and a depressed central fragment existed in 75.3% of the cases. ORIF was performed in 47 patients through a lateral approach using Kirschner wires and in 13 through … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 25 publications
0
16
0
Order By: Relevance
“…They concluded that optimal outcomes were associated with trac tion and that suboptimal results were produced with stat ic fixation and open reduction. 3 Whereas current literature generally agrees that a dynamic component to treatment is optimal for prevention of posthealing PIP joint stiffness, 18 con troversy has remained over the ideal method for treating pilon fractures. 10,19,20 Allison reported on the application of spring loaded dynamic traction with a stainless steel device that permitted AROM and PROM across the joint.…”
Section: Discussionmentioning
confidence: 99%
“…They concluded that optimal outcomes were associated with trac tion and that suboptimal results were produced with stat ic fixation and open reduction. 3 Whereas current literature generally agrees that a dynamic component to treatment is optimal for prevention of posthealing PIP joint stiffness, 18 con troversy has remained over the ideal method for treating pilon fractures. 10,19,20 Allison reported on the application of spring loaded dynamic traction with a stainless steel device that permitted AROM and PROM across the joint.…”
Section: Discussionmentioning
confidence: 99%
“…Mean PIPJ ROM using various approaches has been reported to be approximately 80 , and there is little difference between the efficacy of these methods. 40 If operative treatment is chosen, the outcomes of the chosen procedure should match or be better than that expected of conservative treatment. Table 1 summarizes the indications of current treatment options.…”
Section: Treatment Of Proximal Interphalangeal Joint Fracture Dislocamentioning
confidence: 99%
“…Open reduction and internal fixation (ORIF) ideally allows for anatomic reduction of the joint and articular fragments, while restoring stability with the crucial volar lip buttress and allowing early ROM. Reducing the articular surface (for example, a central depressed fragment) may prevent secondary osteoarthrosis 40 but is less crucial. Factors influencing the results after ORIF include patient age, size of palmar fragment, chronic cases, period of immobilization after surgery, and recurrence of subluxation.…”
Section: Open Reduction and Internal Fixationmentioning
confidence: 99%
See 2 more Smart Citations